Developing a New Method to Remove Some Toxic Metal Ions from Aqueous Media Using an Ionic Liquid - Agab M. Hewas; Salah R. hewas; Khalid M. Omemen (المجلة الأفروآسيوية للبحث العلمي, 2024)
This research investigates the development of sensitive method for extracting heavy metal ions, which traditionally requires the use of strong inorganic acids. The proposed method aims to be simple, rapid, accurate, and widely accessible. In this study, two types of water-immiscible ionic liquid solutions were employed: betaine [bis(trifluoromethylsulfonyl)imide] and 1-butyl-3-methylimidazolium hexafluorophosphate ([BMIM][PF6]). Experimental findings indicate that both ionic liquids demonstrate effectiveness in extracting Ni²⁺, Co²⁺, and Pb²⁺ ions. The results reveal that betaine successfully extracted nickel and cobalt ions from their respective solutions but only partially extracted lead ions. Conversely, [BMIM][PF6] was effective in removing nickel and cobalt ions from water but failed to extract lead ions. These findings underscore the varying extraction efficiencies of the two ionic liquids and highlight their potential applications in targeted heavy metal removal.